Job satisfaction and organizational commitment among customer service representatives at call centre industry in Malaysia / Noor Azlina Mohamed Yunus, Narazatul Akmal Mohamed Yunus and Marhani Mohamed Anuar - Mohamed Yunus, Noor Azlina; Mohamed Yunus, Narazatul Akmal; Mohamed Anuar, Marhani (Faculty of Business and Management, UiTM Shah Alam, 2020)
The call centre is a service-intensive organization with a significant proportion of its employees working in direct contact with its customers. Given the nature of front line employees, job satisfaction is a serious issue in call centre as well as the service industry. The front line employees, like any other service sector employees, need to develop and maintain a strong relationship with its human resources for effective performance in assisting customers' problems and inquiries. Therefore, this paper formulates a framework postulating job satisfaction as an antecedent of organizational commitment in call centre industry. The finding of this study should enrich the existing theories by providing additional evidence on the relationship between employees' job satisfaction and organizational commitment especially for call centre industry. Eventually, the findings provide empirical support to the concepts and theories that are currently discussed in the employees' job satisfaction literature to be applied especially in the context of call centre perspective.